Pengembanagn Media Pembelajaran E-Learning Berbasis Moodle Pada Pokok Bahasan Lingkaran Kelas VIII SMP - Nathasa Pramudita Irianti; Elita Mega Selvia Wijaya (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2017)
This develompent research is aim to produce e-learning media that basic of moodle at circle subject. The research product is a mathematic’s web which contain circle subject for VIII of Junior High School. The product has been tested on VIII-F’s students of SMP Negeri 1 Gedeg. From the test result, the product is valid.